Serum Interleukin-18 Level is Associated With Disease Activity and Interstitial Lung Disease in Patients With Dermatomyositis - Yuan YANG; Geng YIN; Jingcheng HAO; Qibing XIE; Yi LIU (Archives of Rheumatology, 2017)
Objectives: This study aims to demonstrate the utilization of serum interleukin-18 (IL-18) level as a biomarker for disease activity and organ damage in patients with dermatomyositis (DM) or polymyositis (PM) using the Myositis Disease Activity Assessment Tool. Patients and methods: Forty-nine patients (13 males, 36 females) with idiopathic inflammatory myopathies were enrolled in the study. Patients were diagnosed with DM (n=33) or PM (n=16). Twenty age- and sex-matched healthy volunteers (9 males, 11 females) who were determined to be free of autoimmune disease were included as a control group. Disease activity and organ damage were assessed with Myositis Disease Activity Assessment Tool. Serum IL-18 level was measured with enzyme-linked immunosorbent assay and the differences between patient groups were determined. Results: The mean ages of DM or PM patients were 44 and 45, respectively. Interstitial lung disease (ILD) was found in 24 patients (48.98%), including 18 patients with DM (54.55%) and six patients with PM (37.5%). There was no significant difference of disease duration between DM patients (17.5±22.3 months) and PM patients (14.9±28.7 months). Serum IL-18 level in DM (669.2±528.1 pg/mL) was significantly higher than that in the control group (388.3±139.4 pg/mL, p=0.017), but no significant difference was observed between the PM and control group. IL-18 was significantly higher in DM patients with ILD (890.5±618.8 pg/mL) than in patients without ILD (403.8±84.8 pg/mL, p=0.003). It was significantly elevated in patients with severe disease activity (1001.71±694.2 pg/mL) than in those with moderate (485.3±102.2 pg/mL) or mild disease activity (421.0±270.2 pg/mL) (p=0.039). In DM patients, IL-18 was significantly correlated with global disease activity and disease activity in the skin, lung, and heart. Conclusion: Serum IL-18 level was higher in patients with DM and this was associated with disease activity and ILD complication. Thus, it can be used as a valuable serological marker for DM disease activity and ILD complication.